Urgence of Time Term Inclusion in Fulfillment of Rights & Obligations the Parties in Transaction Agreement - Sri Utari (Sultan Agung Notary Law Review, 2021)
The binding agreement for the sale and purchase of land rights is a preliminary agreement made by the prospective seller and prospective buyer before the signing of the deed of sale and purchase before the PPAT. The contents are about the sale and purchase of land rights, but the format is only limited to a binding agreement made by a notary. The Sale and Purchase Binding Agreement is not specifically regulated, so the form and content vary according to the agreement of the parties who made it. However, in its implementation it is often not in accordance with what has been agreed, therefore it is necessary to have special rules so that the parties get legal certainty and protection. The purpose of writing is to describe and analyze the importance of setting the time period as well as the legal consequences that arise by not including the time limit of the rights and obligations of the parties involved. parties to the deed of agreement to bind the sale and purchase of land rights made before a notary. The method used in this study is a normative juridical approach using secondary data sources. The data collection technique used is literature study, then analyzed by qualitative analysis method using legal protection theory, legal certainty theory and justice theory. From the results of the research, it is concluded that: 1. The importance of the rules set by the government to specifically regulate the sale and purchase agreement deed so that the form of the deed made by a notary can provide legal certainty and protection. 2. The legal consequences of the absence of strict legal rules regarding the deed of agreement to bind the sale and purchase of rights to the land.